2014
DOI: 10.1186/1475-2840-13-103
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin: a manifold therapeutic target for metabolic syndrome, diabetes, and coronary disease?

Abstract: Adiponectin is the most abundant peptide secreted by adipocytes, being a key component in the interrelationship between adiposity, insulin resistance and inflammation. Central obesity accompanied by insulin resistance is a key factor in the development of metabolic syndrome (MS) and future macrovascular complications. Moreover, the remarkable correlation between coronary artery disease (CAD) and alterations in glucose metabolism has raised the likelihood that atherosclerosis and type 2 diabetes mellitus (T2DM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
166
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(175 citation statements)
references
References 135 publications
(149 reference statements)
4
166
2
3
Order By: Relevance
“…Finally, treatment with fibrates is associated with an increase in the levels of adiponectin [22,33,36,37,50,55], an adipose-derived factor that may improve endothelial function by multiple mechanisms. It mimics the metabolic actions of insulin [56], which exerts many cardioprotective effects and may also directly increase production of NO in the vascular wall [57]. Furthermore, adiponectin is directly involved in endothelium protection through inhibition of adhesion molecules and proinflammatory cytokine production [50,58], and by stimulation of NO production from endothelium via activation of AMP-activated protein kinase [59].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, treatment with fibrates is associated with an increase in the levels of adiponectin [22,33,36,37,50,55], an adipose-derived factor that may improve endothelial function by multiple mechanisms. It mimics the metabolic actions of insulin [56], which exerts many cardioprotective effects and may also directly increase production of NO in the vascular wall [57]. Furthermore, adiponectin is directly involved in endothelium protection through inhibition of adhesion molecules and proinflammatory cytokine production [50,58], and by stimulation of NO production from endothelium via activation of AMP-activated protein kinase [59].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, resistin is an adipokine that up-regulates the expression of adhesion molecules in human endothelial cells, suggesting its potential role in atherosclerosis (33), and adhesion molecules, such as sE-selectin, sICAM-1 and sVCAM-1 are critical mediators of endothelial dysfunction (25). On the other hand, adiponectin is an insulin-sensitising adipokine that is inversely proportional to adiposity and to the risk of cardiovascular disease development (27). To the best of our knowledge, this is the first intervention trial evaluating the influence of enteral administration of a DSF on diabetes-derived cardiovascular risk consequences.…”
Section: Discussionmentioning
confidence: 99%
“…These adipokines include mainly adiponectin, leptin, TNF-α, IL-6, resistin, MCP-1, PAI-1, and others, which are usually altered in patients with established type 2 diabetes (14,(25)(26)(27). In fact, the levels of plasma adipokines may help to establish the risk to develop cardiovascular comorbidities in diabetics (23).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results extend this evidence by including several others potential confounders, such as insulin resistance and CRP; given that, it was reported that adiponectin has an inverse relationship with markers of inflammation such as CRP 6 and insulin resistance 7 in adolescents and that CRP and insulin resistance were also negatively associated with MF in previous studies 16, . Moreover, it is known that insulin sensitivity is influenced by dietary factors and adiponectin is recognized as having insulin sensitizing properties 7,5 . Previous studies reported that daily intake of fish or omega-3 supplementation increased adiponectin levels as well as a low caloriediet.…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin concentrations have been negatively associated with insulin resistance 5 , CRP 6 and adiposity 7 , positively correlated with HDL-cholesterol 6,8 and it is considered an independent CVD risk factor 9 . It was originally assumed that adiponectin was exclusively synthesized and expressed by adipocytes 10 .…”
Section: Introductionmentioning
confidence: 99%